Hemoglobin α-derived peptides VD-hemopressin (α) and RVD-hemopressin (α) are involved in electroacupuncture inhibition of chronic pain - Yuan, Xiaocui; Guo, Yixiao; Yi, Huiyuan; Hou, Xuemei; Zhao, Yulong; Wang, Yuying; Jia, Hong; Baba, Sani Sa’idu; Li, Man; Huo, Fuquan (Frontiers in Pharmacology, 2024)
Knee osteoarthritis (KOA) is a chronic degenerative bone metabolic disease that primarily affects elderly adults, leading to chronic pain and disability which affect patients’ daily activities. Electroacupuncture (EA) is a commonly used method for the treatment of chronic pain in clinical practice. Previous studies indicate that endocannabinoid system is involved in EA analgesia, but whether endocannabinopeptide VD-hemopressin (α) and RVD-hemopressin (α), derived from hemoglobin chains are involved in EA analgesia is unclear. Therefore, we used RNA-seq to obtain differentially expressed genes Hba-a1 and Hba-a2 involved in EA analgesia in the periaqueductal grey (PAG), which were translated into hemoglobin α chain. EA significantly increased the expression of hemoglobin α chain and the level of hemopressin (α) and RVD-hemopressin (α). Microinjection of VD-hemopressin (α) and RVD-hemopressin (α) into vlPAG mimicked the analgesic effect of EA, while CB1 receptor antagonist AM251 reversed this effect. EA significantly increased the expression of 26S proteasome in KOA mice. Microinjection of 26S proteasome inhibitor MG132 before EA, prevented both anti-allodynic effect and up-regulation the concentration of RVD-hemopressin (α) by EA treatment, and up-regulated the expression of hemoglobin α chain. Our data suggest that EA up-regulated the concentration of VD-hemopressin (α) and RVD-hemopressin (α) through enhancement of the hemoglobin α chain degradation by 26S proteasome in PAG, then activated the CB1 receptor, thereby exerting inhibition of chronic pain in a mouse model of KOA. These results provide new insights into the EA analgesic mechanisms and evidently reveal possible targets for EA treatment of chronic pain.